Contribution of the ELRs to the development of advanced in vitro models - Puertas-Bartolomé, María; Venegas-Bustos, Desiré; Acosta, Sergio; Rodríguez-Cabello, José Carlos (Frontiers in Bioengineering and Biotechnology, 2024)
Developing in vitro models that accurately mimic the microenvironment of biological structures or processes holds substantial promise for gaining insights into specific biological functions. In the field of tissue engineering and regenerative medicine, in vitro models able to capture the precise structural, topographical, and functional complexity of living tissues, prove to be valuable tools for comprehending disease mechanisms, assessing drug responses, and serving as alternatives or complements to animal testing. The choice of the right biomaterial and fabrication technique for the development of these in vitro models plays an important role in their functionality. In this sense, elastinlike recombinamers (ELRs) have emerged as an important tool for the fabrication of in vitro models overcoming the challenges encountered in natural and synthetic materials due to their intrinsic properties, such as phase transition behavior, tunable biological properties, viscoelasticity, and easy processability. In this review article, we will delve into the use of ELRs for molecular models of intrinsically disordered proteins (IDPs), as well as for the development of in vitro 3D models for regenerative medicine. The easy processability of the ELRs and their rational design has allowed their use for the development of spheroids and organoids, or bioinks for 3D bioprinting. Thus, incorporating ELRs into the toolkit of biomaterials used for the fabrication of in vitro models, represents a transformative step forward in improving the accuracy, efficiency, and functionality of these models, and opening up a wide range of possibilities in combination with advanced biofabrication techniques that remains to be explored.